2018
DOI: 10.1093/ije/dyy033
|View full text |Cite
|
Sign up to set email alerts
|

A regional vision of physical activity, sedentary behaviour and physical education in adolescents from Latin America and the Caribbean: results from 26 countries

Abstract: The study sets a challenge for the LAC region, as physical inactivity and SB are highly prevalent across all countries. Gender inequity was shown in most countries, with boys reporting more active behaviours. Regional and national actions for implementing policies to revert this situation are urgent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
95
1
11

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(120 citation statements)
references
References 22 publications
13
95
1
11
Order By: Relevance
“…Using a large-scale global education database, we identified substantial cross-country differences in adolescents' physical activity. Our findings extend those conducted in either high 10 11 13 or low-middle 12 income countries by including a greater number of countries across income levels, using more recent data (2015), and expanding on the comparisons across countries. We examined activities conducted inside and outside of school separately, compared the distributions of activity in addition to averages, quantified gender-and SES-disparities, and examined correlations with national-level economic factors thought to be key determinants of adolescent health.…”
Section: Discussionsupporting
confidence: 73%
“…Using a large-scale global education database, we identified substantial cross-country differences in adolescents' physical activity. Our findings extend those conducted in either high 10 11 13 or low-middle 12 income countries by including a greater number of countries across income levels, using more recent data (2015), and expanding on the comparisons across countries. We examined activities conducted inside and outside of school separately, compared the distributions of activity in addition to averages, quantified gender-and SES-disparities, and examined correlations with national-level economic factors thought to be key determinants of adolescent health.…”
Section: Discussionsupporting
confidence: 73%
“…13 School Environment D 12.8% to 33.0% of adolescents reported the participation in physical education for 3 or more days per week without gender differences. 3,4 26.0% of students reported that they have positive reinforcement from teachers for being physically active. 14…”
Section: Resultsmentioning
confidence: 99%
“…2-4 27.4% of children (9 to 11 years old) and 18.9% of adolescents meet the PA guidelines based on National data. [2][3][4] There is lack of information in 5 to 8 years old.…”
mentioning
confidence: 99%
“…According to the WHO, Latin America and the Caribbean regions ranks first among regions in inactivity in the world with a prevalence rate of insufficient physical activity of 32% . Also, a recent report of physical behaviors of 64,034 adolescents from the region showed that only 15% of adolescents were physically active …”
Section: Factors Responsible For the Higher Prevalence Of Nafld In Lamentioning
confidence: 99%